The Social Capital of Labour-Farmer in the Middle of Parungpanjang Research Forest Governance - NFN Desmiwati; Mirna Aulia Pribadi; Kun Estri Maharani (Jurnal Perbenihan Tanaman Hutan, 2018)
Research forest of Parungpanjang (RF) is a part of forest area with special purposes (KHDTK), under authority of Forest Tree Seed Technology Research and Development Center Bogor. The management is carried out by involving the local community as labour farmer. The existence of labour farmer in RF give a positif impact on the management of RF. However there is no improve yet on socio-economic condition of the labour farmer. Whereas the ideal form complemented with stable social structure and good social interaction would be a foundation to build social capital. The problem is how far the strenght of the social capital of the labour farmer and how is the socio-economic relation toward RF’s management? This qualitative research collect information through interviewing the labour farmer in RF of Parungpanjang, village government, community figures and supported with questionairre and observation on the field during March─August 2017. The result of the study shows that the social capital of the labour farmer is low, indicated by norm is average, social net work is low, trust is average, the mutual resiprocity is also low, as well as the collective value is low. Regarding to that, the empowerment cannot merely operated on the material incentive for land-based production, it is required to develop the collective work ethos. The non-formal leadership on the labour farmer groups must be strengthened to buid the stronger labour farmer’s social capital ahead.